Scheduling the Norwegian football league. (25th September 2012) - Hausken, Magnus D.; Andersson, Henrik; Fagerholt, Kjetil; Flatberg, Truls
Abstract Scheduling the Norwegian football (soccer) league is a difficult process as there are many requirements to be considered. The schedule should be fair to all teams while fulfilling as many requests from the stakeholders as possible. For a schedule to be fair, the number of breaks (i.e., consecutive home or away games) should be as low as possible and a team should not be scheduled with many difficult games in a row. Further, the television companies want to have some attractive games in each round and there are several team‐specific constraints or wishes to consider. This paper proposes a two‐phase solution method that relies on a pattern‐based model to provide good schedules. Phase 1 generates feasible patterns, while the pattern‐based model in Phase 2 assigns a pattern to each team considering the various constraints and wishes. A specialized branching strategy that proves to reduce the solution time is also introduced. The computational study shows that the suggested method can handle the various requirements for the Norwegian football league, and is able to produce significantly better results than the schedules created manually by the Norwegian Football Association.